PEMBERDAYAAN UMKM KELURAHAN SUNGAI KAPIH MELALUI INOVASI PANGAN FUNGSIONAL JAMUR TIRAM FORTIFIKASI DAUN PANDAN UNTUK MENDUKUNG SDG’S3 - Leswana, Nurillahi Febria; Taufiqurrahman, Muh; Hutagalung, Remita Ully (Jurnal Pepadu, 2025)
This community service program in Sungai Kapih Village, Samarinda City, was implemented to strengthen the capacity of micro, small, and medium enterprises (MSMEs) through the development of functional food innovations based on oyster mushrooms (Pleurotus ostreatus) fortified with pandan leaves (Pandanus amaryllifolius). The program was motivated by the limited product diversification and underutilization of local ingredients as sources of functional food. A participatory approach was applied, consisting of needs assessment, socialization on the concept of functional food, technical training, production and packaging assistance, as well as monitoring and evaluation. The results showed significant improvements in participants’ knowledge of functional foods and technical skills in producing oyster mushroom–pandan fortified products, such as noodles and nuggets. Pre-test and post-test evaluations revealed an increase in processing skills from 40% to 80%, and a rise in positive attitudes toward innovation from 35% to 85%. The developed products demonstrated higher nutritional value and better sensory attributes, offering strong market potential and enhancing MSME competitiveness. Beyond economic benefits, this innovation also contributes to public health, as oyster mushrooms provide protein, fiber, and bioactive compounds, while pandan leaves enrich antioxidant properties and sensory appeal. The program aligns with the Sustainable Development Goal (SDG) 3 on Good Health and Well-Being, while simultaneously supporting local food security and sustainable community empowerment